Students’ Learning Achievement in Writing Analytical Exposition Text: A Study in Jigsaw Cooperative Learning Model - Herni Hafsah; Fatmasari, Elly; Iskandar, Iskandar (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The purpose of this study is to improve students' learning outcomes in writing analytical exposition texts using the cooperative learning jigsaw learning model strategy. The research method used was classroom action research, which was carried out in two cycles. Data collection techniques used are observation, interview, test, and documentation. The observation was done by the real teacher and collaborator in observing the teacher’s (writer's) performance. The result showed that there were significant improvements in students’ learning outcomes. It can be seen in the mean score and percentage of the test from cycle 1 until cycle 2. The students’ percentage who passed the criteria for success in cycle 1 is 67.7%. And cycle 2 is 90%. It can be concluded that the cooperative learning jigsaw learning model can improve the student's learning outcomes in writing analytical exposition texts.